2020
DOI: 10.1163/22134808-20191425
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Hand Illusion in Obesity: Dissociation Between Multisensory Interactions Supporting Illusory Experience and Self-Location Recalibration

Abstract: Abstract The Rubber Hand Illusion (RHI) is used widely to investigate the multisensory integration mechanisms that support bodily self-consciousness and, more specifically, body ownership and self-location. It has been reported that individuals affected by obesity show anomalous multisensory integration processes. We propose that these obesity-induced changes could lead to an unusual susceptibility to the RHI and anomalous bodily self-experience. To test this hypothesis, we adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 70 publications
2
20
0
Order By: Relevance
“…Seven studies used BIs toward a body part to investigate alterations in body representation in patients with eating disorders (ED) compared to a healthy control group (Carey & Preston, 2019;E. Eshkevari et al, 2012;Ertimiss Eshkevari et al, 2014;Keizer et al, 2014;Tagini et al, 2020;Zopf et al, 2016). Specifically, a significant reduction in hand size estimation and low levels of both implicit and explicit body satisfactions have been shown when using the moving rubber hand illusion (Carey & Preston, 2019).…”
Section: Results In Clinical Populationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies used BIs toward a body part to investigate alterations in body representation in patients with eating disorders (ED) compared to a healthy control group (Carey & Preston, 2019;E. Eshkevari et al, 2012;Ertimiss Eshkevari et al, 2014;Keizer et al, 2014;Tagini et al, 2020;Zopf et al, 2016). Specifically, a significant reduction in hand size estimation and low levels of both implicit and explicit body satisfactions have been shown when using the moving rubber hand illusion (Carey & Preston, 2019).…”
Section: Results In Clinical Populationsmentioning
confidence: 99%
“…In their study, Zopf and colleagues (2016) used the RHI to test whether body localization abilities are altered in patients with AN compared to a healthy control group: patients with AN displayed a compromised proprioceptive encoding of hand location (Zopf et al, 2016). In addition, Tagini and collegaues (2020), used the VHI in participants affected by obesity and participants with a healthy weight, to observe a possible unusual susceptibility to the RHI related to anomalous bodily self-experience, and found that even though participants with obesity reported a strong ownership illusion, a reduction in recoding self-location was also observed (Tagini et al, 2020).…”
Section: Results In Clinical Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Visual stimuli consisted of videos displayed via MR-compatible goggles, placed at 3–5 cm in front of the participant’s eyes, and adjusted to achieve a clear dual-view image covering the entire visual field (Resonance Technology, Inc.). According to the VHI procedure, the videos showed a virtual right human hand being brushed by a paintbrush ( Tagini et al. 2019 ; Pyasik et al.…”
Section: Methodsmentioning
confidence: 99%